“Asyraf & Adab 2: let’s learn”s android animation application by enisaNimation - Shamsudeen, Ummul Fazila; Muhamed Johari, Nur Asyeila; Abd Malik, Sofianiza (2014)
This project involves in creating and designing 3D animation which has been launched specifically in Android as an application. The content of this application widely focused in terms of the Islamic teachings where by it highlights mainly on the Islamic manners and du'a. ￼